Key drivers of visual acuity gains in neovascular age-related macular degeneration in real life: findings from the AURA study. Issue 12 (30th March 2016) - Holz, Frank G; Tadayoni, Ramin; Beatty, Stephen; Berger, Alan; Cereda, Matteo Giuseppe; Hykin, Philip; Staurenghi, Giovanni; Wittrup-Jensen, Kim; Altemark, Andreas; Nilsson, Jonas; Kim, Kun; Sivaprasad, Sobha
Abstract : Background/aims: To identify predictive markers for the outcomes of anti-vascular endothelial growth factor therapy for neovascular age-related macular degeneration (nAMD). Methods: AURA was a retrospective, observational, multicentre study that monitored the 2-year outcomes following intravitreal ranibizumab treatment in patients with nAMD. Using stepwise regression analysis, we evaluated the association between visual acuity outcomes, baseline characteristics and resource utilisation in order to determine which variables are significantly linked to outcomes in AURA. We also examined the relationship between visual acuity outcomes and number of injections received. Results: Analyses were performed using data from year 1 (n=1695) and year 2 completers (n=1184). Logistic analysis showed that baseline visual acuity score, age at start of therapy, number of ophthalmoscopies and optical coherence tomography (OCT) (combined) and number of injections (ranibizumab) were significant (p<0.05) prognostic factors for vision maintenance (loss <15 letters) or vision gain (≥15 letters). Patients who received >7 injections (in 1 year) or >14 injections (over 2 years) gained more letters and demonstrated greater vision maintenance (loss of <15 letters) than patients who received fewer injections. There was a significant (p<0.05) association between number of injections and national reimbursement schemes and OCT. Conclusions: A number of factors that are predictive of treatment outcomes in a real-life setting were identified. Notably, the decline of treatment benefits may be linked to number of injections and a failure to visit clinicians and receive OCT as required. These findings may be helpful in guiding ophthalmologist treatment decisions under limited time and financial constraints. Trial registration number: NCT01447043.